2010
DOI: 10.1089/jop.2010.0032
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dorzolamide–Timolol (COSOPT) in Patients Who Were Treatment Naive for Open-Angle Glaucoma or Ocular Hypertension: The COSOPT First-Line Study

Abstract: DT alone and DT in combination with a PG are effective in significantly reducing IOP in patients with untreated OAG or ocular hypertension. The treatment was safe and well tolerated with a low incidence of AEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
2
11
0
1
Order By: Relevance
“…In patients requiring treatment with more than one agent, a fixed combination therapy is usually preferred because it is associated with increased compliance 1012. However, it has been shown that, in reality, combination therapy is often administered as first-line therapy for patients diagnosed with primary open angle glaucoma or ocular hypertension 11,13…”
Section: Introductionmentioning
confidence: 99%
“…In patients requiring treatment with more than one agent, a fixed combination therapy is usually preferred because it is associated with increased compliance 1012. However, it has been shown that, in reality, combination therapy is often administered as first-line therapy for patients diagnosed with primary open angle glaucoma or ocular hypertension 11,13…”
Section: Introductionmentioning
confidence: 99%
“…In patients requiring treatment with more than one agent, combination therapy is usually preferred since it is associated with increased compliance 10,11. However, it has been shown that in reality, combination therapy is often administered as first-line therapy for patients diagnosed with POAG or ocular hypertension (OHT) 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Henderer et al 14 showed a mean percentage change of -40% in the patients after 2 months of initial treatment with Cosopt. Crichton et al 15 reported a -36.4% change in IOP after 6 weeks, and a -40.4% change in the patients treated with Cosopt after 12 weeks. Kim et al, 16 however, reported an IOP change of -23.7% at week 12 postswitch in the normal-tension glaucoma patients treated with DTFC, which was inferior to the results of the present study.…”
Section: Discussionmentioning
confidence: 96%